The introduction to muscle physiology and design
General Overview The Cross-bridge Cycle Cellular Energy Stores Glucose Metabolism Fat Metabolism Creatine Phosphate Fiber Types Microscopic Structure Macroscopic Structure Intrinsic Properties of Muscle Excitation-Contraction Coupling Hypertrophy Anabolic Steroids Electrical Stimulation Eccentric Contraction Joint Moment Arms Muscle-Joint Interactions Bibliography